Human Capital: Conception Frame and Functional Methodology - Kazakov, Atanas (Research Papers, 2010)
This study treats key issues related to the theory and methodology of human capital. The concept of this form of capital has been presented in a broader frame; the classical, neo-classical and contemporary bases of the theory of human capital have been discussed. An analysis of and a comparison between physical and human capital have been carried out. The thesis about the indestructible unity between human capital and its physical exponent – the living human being with its wide range of traits and features, has been developed. In the body of Bulgarian writing on economics, this is the first study which examines the common features and the distinctions between human capital and intellectual capital. Furthermore, people and human capital are viewed as both the subject and the object in the relationship between society and the marketplace. The study argues the position for the need of interdisciplinary approach towards the issues related to human capital.